Ultrafast Excited State Relaxation Dynamics of New Fuchsine‐ a Triphenylmethane Derivative Dye. Issue 24 (22nd October 2021) - Biswas, Chinmoy; Rao Soma, Venugopal; Chetti, Prabhakar; Santosh Kumar Raavi, Sai
Abstract: An all‐inclusive investigation of the ultrafast excited state relaxation dynamics of a triphenylmethane derivative molecule, New Fuchsine (NF), using a combined approach of density functional theory (DFT), femtosecond transient absorption spectroscopy (fs‐TAS), and photoluminescence spectroscopy is presented in this work. The DFT calculations confirmed the formation of twisted molecular structure in the excited state of NF in ethanol solution with bond rotation of ≈86°. TAS measurements of NF solution exhibited ultrafast ground state‐recovery pathway via a conical intersection confirming an ultrafast structural reorientation. On the contrary, TAS measurements of NF thin‐film exhibited a longer excited‐state lifetime suggesting a hindered molecular twisted state formed as an intermediate step. Photophysical kinetic models are proposed to globally fit the fs‐TAS data establishing the twisted intramolecular charge transfer (TICT) state mediated ground state recovery for NF in solution and thin film, respectively. Temperature‐dependent photoluminescence study of NF film provided a clear insight into the effect of rotational motion of phenyl rings in NF molecules over the TICT mediated emission. Abstract : New Fuchsine molecules in solution and thin‐film show different excited‐state relaxation pathways due to the twisting of phenyl rings after photoexcitation. Transient absorption measurement reveals dominant conical intersection mediated nonradiative channel in solution whereas triplet assisted radiative channel is observed for thin‐films. Photoluminescence measurements of thin‐films at cryogenic temperatures reflect enhancement of radiative recombination due to the restriction of twisting in the molecules.